The use of botulinum toxin in keloid scar management: a literature review - Catrin Sohrabi; Ioannis Goutos (SAGE Publishing, 2020)
Introduction: Administration of botulinum toxin is an increasingly popular procedure in the medical and aesthetic field. There is emerging evidence that it can influence fibroblast activity and minimise tension around the scar by virtue of muscular chemoimmobilisation. This review aims to explore the current evidence base behind the treatment of keloid scars with botulinum toxin. Methods: A detailed literature review was conducted using PubMed Medline, Embase and Web of Science databases. Manuscripts were appraised and classified in accordance with the Joanna Briggs Institute Levels of Evidence by an independent consultant in evidence synthesis. The results of this search are presented in descending order of evidence for botulinum toxin as a primary management agent as well as a secondary adjunct following extralesional keloid excision. Discussion: On the basis of level 1 evidence, botulinum toxin appears to be equivalent to triamcinolone in producing a short-term reduction in keloidal volume, height and vascularity. A number of level 1 and 2 studies also suggest that botulinum toxin may be particularly helpful in alleviating symptoms of keloid associated pain and itch. There are currently limited studies appraising the value of botulinum toxin in the postoperative management of keloid scars. Conclusion: Botulinum toxin may represent a promising agent in the management of keloid scars. However, further research involving large-scale studies with comparative designs and long-term follow-up is warranted to delineate the value of this therapeutic modality in scar management protocols.